Hybrid 2D Theory of Outdoor Infections in Times of Global Pandemic - Nieto-Chaupis, Huber (2022)
This paper targets to study the concrete scenario of aerosols transporting virus fact that is seen as a potential cause of massive infections in open spaces through the usage of a two dimension theory. For this end, the conjunction of a deterministic model and the equation of Weiss with a probabilistic meaning is compactified in one single equation. With this approach, different distributions of fractions of infections as function of distance are presented. Although in most cases, this hybrid theory yields distances of 1.5 and 2.0 m. The distributions also suggest the role of wind as a strong factor that might keep the aerosols beyond the established social distancing as cause of delaying of dehydration. Therefore, outdoor characteristics are factors that might not be seen at first sight but would constitute a risk factor in epochs of peaks of pandemic.